2018
DOI: 10.1016/j.repc.2017.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous coronary artery dissection: A single-center case series and literature review

Abstract: In the studied population, SCAD was more prevalent in middle-aged women. Despite the high prevalence of in-hospital re-infarction or during follow-up, the prognosis was good overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Overall, 1458 titles and abstracts were first identified; after exclusion according to pre-specified criteria, 16 observational studies were included in the present pooled analysis (Figure 1). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] No randomized clinical trial was found. A total of 444 patients were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 1458 titles and abstracts were first identified; after exclusion according to pre-specified criteria, 16 observational studies were included in the present pooled analysis (Figure 1). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] No randomized clinical trial was found. A total of 444 patients were included.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, most registries only report on combined outcomes at last available follow-up, but individual outcomes within the first crucial year after SCAD are rarely described and are mostly limited to small case reports and series. 18,20,21 Likewise, long-term comparisons of clinical outcomes of conservative versus invasive treatment strategies for SCAD have been reported in individual studies and meta-analyses describing similar clinical outcomes and lower target vessel revascularizations in medically-managed patients compared to those undergoing revascularization. 6,30 Nevertheless, MACE incidence within the first year after SCAD according to treatment strategy is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 provides an overview of the characteristics of the 34 included studies 2,4‐6,11‐40 . The mean duration of follow‐up was 33 ± 20 months.…”
Section: Resultsmentioning
confidence: 99%
“…The true prevalence of SCAD remains unknown as this is still an underdiagnosed disease. In recently published studies, SCAD accounted for 0.3%-1.2% of all ACS cases [3,[14][15][16] (Table 1). This condition affects predominantly young and middle-aged women (more than 70% of cases reported in sev-eral studies) [5].…”
Section: Incidence Precipitating Risk Factors Comorbidities and Clinical Presentationmentioning
confidence: 95%